A Cluster-Randomized Trial to Reduce Cesarean Delivery Rates in Quebec. Issue 9 (September 2015) - Chaillet, Nils; Dumont, Alexandre; Abrahamowicz, Michal; Pasquier, Jean-Charles; Audibert, Francois; Monnier, Patricia; Abenhaim, Haim A.; Dubé, Eric; Dugas, Marylène; Burne, Rebecca; Fraser, William D.
<x xml:space="preserve">Abstract</x> ABSTRACT In developed countries, cesarean delivery rates are high and increasing. Strategies to reduce cesarean delivery rates have been the subject of recent studies and guidelines. While these studies suggest strategies involving audits and feedback are generally effective, there have not been large randomized trial data assessing the effects of a multifaceted strategy. This trial aims to assess whether the rate of cesarean delivery would be reduced by a multifaceted intervention promoting on-site training with audits and feedback. The QUARISMA (Quality of Care, Obstetrics Risk Management and Mode of Delivery) trial was conducted between April 1, 2008, and October 31, 2011, at 32 public hospitals in Quebec. Hospitals included had to have a 17% cesarean delivery rate or higher and at least 300 deliveries the year before. For inclusion, infants had to be born at least 24 weeks' gestation and weigh at least 500 g at delivery. Hospitals were randomly assigned to either a control or intervention group. The study spanned 3.5 years, first with a yearlong baseline period followed by a 1.5-year intervention period, and concluded with a yearlong postintervention period. Instructors from the Society of Obstetricians and Gynecologists of Canada provided training in evidence-based clinical practices. The intervention program also included clinical audits. There was no financial incentive. There was no intervention in the control groups. A total of 184, 952 women delivered during the study period. In the control group, the baseline cesarean delivery rate was 23.2%, and in the intervention group, the rate was 22.5%. After intervention, the rate of cesarean delivery was 23.5% in the control group and 21.8% in the intervention group (P = 0.04). In both groups, rates of labor induction increased, but increased more in the control group than in the intervention group (adjusted odds ratio, 0.82; 95% confidence interval, 0.76–0.87; P < 0.001; adjusted risk difference, −3.8%; 95% confidence interval, −5.1% to −2.7%). A statistically significant reduction in the cesarean delivery rate was seen in low-risk pregnancies (−1.7%, P = 0.03) but not among high-risk pregnancies (P = 0.35). The reduction was significant but small. Interestingly, both major and minor neonatal morbidity in both low- and high-risk pregnancies was significantly reduced after intervention (adjusted risk difference, −0.7% for major morbidity [P = 0.03] and −1.7% for minor morbidity [P < 0.001]). This trial confirmed previous studies suggesting benefits of a multifaceted strategy involving audits and feedback. It is not clear, however, which aspects of the intervention program were responsible for the reduction in the rate of cesarean deliveries.